Thermal performance and cost analysis of mortars made with PCM and different binders - Cunha, Sandra Raquel Leite (2016)
The high energetic consumption is one of the biggest concerns of modern society. The incorporation of phase change materials (PCM) in construction materials allows regulates the temperature inside the buildings. The main objective of this study was the characterization of the thermal performance of PCM mortars based in different binders. It was possible to observe that the incorporation of PCM in mortars leads to a decrease of the maximum temperatures, increase of the minimum temperatures, significant lag time delay, reduction of the heating and cooling needs, and consequent decrease of the cost of HVAC systems operation, for all tested seasons.